SCHOOL INTEGRATED MEDICAL OUTREACH:AN APPROACH TO ENHANCE HEALTH SERVICE DELIVERY IN TURKANA, KENYA: (Proceedings of the Global Public Health Conference, 2024)
School integrated medical outreach ,is an approach that aims at delivering basic health care services to school going children by linking schools to catchment community health units and health facilities.The approach is in line with the Universal Health coverage strategy ,that puts communities at the center-stage of health care delivery services,with minimal delays and cost. In Turkana county,access to static health facilities is between 5 to 50 kilometers,this is a huge challenge to children as they are vulnerable to abuses,when they go to seek medical attention at static health facilities and at the health facilities,there are no specific services for children,even when they are in uniform,they are not given the attention they deserve,notwithstanding the fact that they have missed class hours ,impacting on their academic performance.Mapping and zoning of schools within 0-20 kilometers from the static health facility, and in a strategy dubbed #TakingHospitalstoschoolschallenge#,the link community units staff plan,organize and conduct schools dialogue days(SDAs) and School Action Days(SADs),where schools are recognized as School Health Units(SHUs).The link health facility in consultation with school management and community unit organize school medical outreach on agreed schedule.The focus of the approach is schools located in nomadic pastrolist areas and hard to reach areas,which form 65% of schools .From 2019 to 2023,the link facility health care workers have managed to visit 45 schools,with a population of 87,706,treating 76,364 ,and further referring 6,017 to the link health facility for more review
Keywords: school integrated medical; school dialogue days; health service delivery; community health; Turkana county; nomadic pastrolists